Peran Disiplin, Etos, dan Motivasi Kerja dalam Meningkatkan Kinerja Karyawan pada BPR Adi Sedana Ayu - I Dewa Ayu Tita Permata Tabita; I Gusti Agung Sasih Gayatri (Jurnal Transformasi Bisnis Digital, 2026)
This research seeks to investigate the effects of work discipline, work ethic, and work motivation on employee performance at BPR Adi Sedana Ayu. The study is motivated by existing challenges, including insufficient discipline, reduced work enthusiasm, and limited employee motivation, which negatively affect organizational performance. A quantitative research design was applied, involving a saturated sampling technique with 35 employees as respondents. Data were gathered through structured questionnaires and analyzed using multiple linear regression to evaluate both partial and simultaneous influences. The results demonstrate that work discipline, work ethic, and work motivation exert a positive and statistically significant impact on employee performance, both individually and jointly. Based on these findings, the study emphasizes the need for improved supervision, the development of a constructive work culture, and the enhancement of employee motivation through performance-based incentives, career development opportunities, and a supportive work environment. Therefore, this study emphasizes the importance of better supervision, the formation of a positive work culture, and strengthening employee motivation through providing incentives, career development, and creating a supportive work environment.